MOOCs as “Semicommons” in the Knowledge Commons Framework - Rother, Kyle (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2016)
The commons approach to knowledge governance is an increasingly popular and successful model for mediating and explaining the ways in which knowledge producers and users, institutions, and shared information resources, interact in social and cultural domains. There is a growing body of literature on the knowledge commons, to which this article seeks to contribute by offering an analysis of massive open online courses (MOOCs). The study outlined in this article deployed the knowledge commons research framework developed by Madison, Frischmann and Strandburg (2010). This framework attempts to align studies of knowledge commons by providing a structured yet flexible set of research questions that emphasise the dynamic relation between default governance regimes (such as proprietary intellectual property rights), tools and infrastructure, and social and cultural norms. The study determined that the MOOC environment exhibits some characteristics of a knowledge commons, and thus the Madison et al. (2010) framework can be productively applied in this context. In addition, the study found that, due to the generally conventional copyright paradigms and varying degrees of openness within the proprietary MOOC platforms, MOOCs can be considered a type of what Madison et al. (2010) term a “semicommons”. Furthermore, because access to learning resources, a key element of access to knowledge (A2K), is an important driver of development, and because openness is an important facilitator of that access, the semicommons status of MOOCs (as learning resources) to some extent mitigates their contribution to increased A2K.
Keywords: knowledge commons, semicommons, massive open online course (MOOC), copyright, access to knowledge (A2K), development